Perkembangan (Kognitif, Fisik-Motorik, Sosio-Emosional) dan Penanaman Nilai Agama pada Masa Pranatal - Sipayung, Ami Syadila (Lembaga Yasin AlSys, 2023)
This study aims to find out how cognitive, physical-motor, socio-emotional development is in the prenatal period and to find out how religious values are instilled in the prenatal period. The method used in this research is qualitative research with a library research approach, namely research whose subject is in the form of library literature. Sources of data depart from documentation from books and scientific journals that discuss development (cognitive, physical-motor, socio-emotional) and the inculcation of religious values in the prenatal period. The results of this study indicate that it is very important for parents to maintain development in the prenatal period. Attention from both parents, mother and father is needed in the prenatal period so that the growth and development of the baby in the womb is healthy and does not lack anything. prenatal development from a cognitive perspective, such as when a baby sucks a finger in the womb. From a physical point of view, physically it seems that every month the baby experiences development and growth. In terms of social emotions without many realizing it, mother and fetus already have a very strong emotional connection. It is also important for parents to instill religious values in the prenatal period, the methods that can be used by parents in instilling religious values in the prenatal period are: Story telling (communication) method, prayer method, dhikr method, dialogue method, and worship method.